Private equity regulation: what are the consequences of the alternative investment fund managers directive (AIFMD) on private equity managers? - Martignier, Romain Paul (2015)
The recent global financial crisis brought significant regulatory changes in the worldwide financial industry. In Europe and in the alternative asset sector specifically, a new regulation by the name of Alternative Investment Fund Managers Directive saw the daylight in 2010. This far-reaching and complex Directive with the main goal of regulating and overseeing alternative investment funds has triggered many discussions and represents an industry game-changer. Thus, this research will focus on the impact and consequences of the Directive on private equity fund managers and the role of regulators. In other words, what are the effects, what does that mean in a quantitative and qualitative sense, and how is it likely to influence the outlook of this asset class? In order to provide the reader with an extensive view on the topic, the paper will first discuss relevant theory and literature, using mix-methods and legal-dogmatic approaches. Further, descriptive case studies, analysis of existing surveys, and interviews with industry experts will supplement the paper in order to understand primary implications of the Directive with the goal of providing useful insights for further private equity regulation research.